Removal Of Fe2+ (Iron) From Batik Industries' Effluent By Using Activated Carbon From Mangrove Timber Prepared Via Physiochemical Activation - Abdullah, Mohamad Alif (Universiti Sains Malaysia, 2017)
In the present study, different activated carbons were prepared from carbonized mangrove timber by potassium hydroxide activation agent. The activated carbons were characterized by thermogravimetric analyzer, brunauer-emmett-teller and elemental analyzer. The Fe2+ ions adsorption of the prepared carbons was evaluated. The different factors affecting Fe2+ ions removal were studied which are the activation temperature and ratio of KOH impregnation. The optimum Fe2+ ions removal was obtained at activated carbon with parameter 850 °C of activation temperature and 1.5 of KOH impregnation ratio. The maximum removal percentage were determined at 50 mg/L initial Fe2+ concentration at 57.86 %. The adsorption of Fe2+ ions on mangrove based activated carbon was found to follow the Langmuir adsorption isotherm and pseudo second order kinetic model. The result of adsorption study showed that the activated carbon prepared from mangrove timber is a suitable adsorbent for Fe2+ ions removal from aqueous solution.